2006
DOI: 10.1002/dvdy.20878
|View full text |Cite
|
Sign up to set email alerts
|

Early temporal‐specific responses and differential sensitivity to lithium and Wnt‐3A exposure during heart development

Abstract: Members of both Wnt and bone morphogenetic protein (BMP) families of signaling molecules are important in heart development. We previously demonstrated that ␤-catenin, a key downstream intermediary of the canonical Wnt signaling pathway, delineates the dorsal boundary of the cardiac compartments in an anteroposterior progression. We hypothesized the progression involves canonical Wnt signaling and reflects development of the primary body axis of the embryo. A similar anteroposterior signaling wave leading to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 71 publications
4
37
0
Order By: Relevance
“…The adverse effects of Ca channel blockade are similar to the effects that we reported previously with lithium ion exposure and with exogenous Wnt3A exposure [26]. All 3 branches of Wnt signaling pathways may be involved in heart organogenesis.…”
Section: Calcium and Cardiac Precursor Cell Differentiationsupporting
confidence: 83%
See 1 more Smart Citation
“…The adverse effects of Ca channel blockade are similar to the effects that we reported previously with lithium ion exposure and with exogenous Wnt3A exposure [26]. All 3 branches of Wnt signaling pathways may be involved in heart organogenesis.…”
Section: Calcium and Cardiac Precursor Cell Differentiationsupporting
confidence: 83%
“…Wnt signaling early in gastrulation promotes cardiac differentiation [29]. If Wnt signaling, however, is potentiated into stages 4 and 5 of gastrulation, as by exogenous Wnt3A or LiCl exposure, it becomes inhibitory to cardiomyogenesis [26]. Normally, in the embryo Dickkopf-1 antagonizes canonical Wnt signaling to initiate differentiation [30].…”
Section: Calcium and Cardiac Precursor Cell Differentiationmentioning
confidence: 99%
“…Our experimental evidence, relating peak cardiac defects to an early timing of exposure during vertebrate gastrulation stages (Chen et al, 2008;Manisastry et al, 2006), means that the most susceptible exposure period for heart defects occurs before most women are aware they are pregnant. Moreover, evidence published since the mid-1990s suggests that the risk of birth defects arising from Li exposure during early pregnancy is high and can result in early embryonic lethality.…”
Section: Introductionmentioning
confidence: 94%
“…Canonical Wnt signaling can have both positive and negative effects on cardiac specification and differentiation, dependent on the developmental stage when being induced (Manisastry et al, 2006;Verma and Lenka, 2010;Dohn and Waxman, 2012;Willems et al, 2011). Using the heat shock-inducible Wnt8 line Tg(hsp70:wnt8-gfp), we indeed observed that induction of Wnt8 at 16 hpf reduced the number of ventricular cardiomyocytes (supplementary material Fig.…”
Section: Loss Of Knypek/glypican4 Results In Reduced Cardiomyocyte Numentioning
confidence: 81%